1992
DOI: 10.1056/nejm199204163261602
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in Resistant Juvenile Rheumatoid Arthritis

Abstract: Methotrexate given weekly in low doses is an effective treatment for children with resistant juvenile rheumatoid arthritis, and at least in the short term this regimen is safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0
5

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 519 publications
(106 citation statements)
references
References 21 publications
1
100
0
5
Order By: Relevance
“…In the screening phase, we enrolled an amount of patients (n ϭ 633) that was very close to the hypothesized sample size needed (n ϭ 650). In the randomization phase, however, we were unable to recruit the calculated number of patients (n ϭ 230) due to a higher-than-expected response rate to standard-dose MTX (72% versus 63% expected) and a high rate of noneligible patients among the nonresponders (53 [40%] of 133) (4).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the screening phase, we enrolled an amount of patients (n ϭ 633) that was very close to the hypothesized sample size needed (n ϭ 650). In the randomization phase, however, we were unable to recruit the calculated number of patients (n ϭ 230) due to a higher-than-expected response rate to standard-dose MTX (72% versus 63% expected) and a high rate of noneligible patients among the nonresponders (53 [40%] of 133) (4).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…At a dosage of 10 mg/m 2 /week, MTX has been shown to have a significant therapeutic advantage over placebo and an acceptable safety profile (4). Subsequently, a higher dosage of MTX, up to 30 mg/m 2 / week, has been suggested as a therapeutic option for patients whose condition remains resistant to the standard dosage, but no randomized trial has ever confirmed this hypothesis (5).…”
mentioning
confidence: 99%
“…Weekly methotrexate (MTX), at parenteral dosages of up to 15 mg/m 2 /week, has been established as an effective and safe therapy for polyarticular-course JRA (5)(6)(7). For children whose disease does not respond to MTX, anti-tumor necrosis factor (anti-TNF) therapy is a treatment option (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Since the introduction of more potent treatment strategies, the evaluation of radiographic joint damage has become more prominent in the assessment of disease progression in JIA (2)(3)(4). Because one of the aims of JIA treatment is to prevent or retard joint damage, and radiographs are able to document this damage, a standardized tool for the radiologic evaluation of the lesions of the joints over time is needed.…”
mentioning
confidence: 99%